PENYULUHAN HUKUM MENGENAI UNDANG-UNDANG NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG BAGI GURU BIMBINGAN KONSELING DAN SISWA/SISWI SMK/SMA/MA SE-KABUPATEN CIANJUR - Nuraeny, Henny (JE (Journal of Empowerment), 2017)
Trafficking is a violation of human dignity that is contrary to human rights and legislation. One of the victims of the crime of trafficking in the district of Cianjur is an underage child. An Integrated Service Center for Women and Children Protection (P2TP2A) of Cianjur district in collaboration with the Faculty of Law of Suryakancana University conducting an even in preventing the human trafficking crime. One of the efforts to overcome the trafficking is by socializing the law No. 21 of 2007 on the Eradication of Trafficking for the counseling teacher and student in order to get a better understanding of the meaning, way, form, effects, prevention and sanction the crime of trafficking.